Pengaruh Kualitas Pelayanan Kesehatan terhadap Tingkat Kepuasan Masyarakat pada Program Pemberantasan Sarang Nyamuk (PSN) 3M Plus di Desa Asembagus Kecamatan Kraksaan Kabupaten Probolinggo - Mahfud Jailani Aminulloh; Mastina Maksin; Maulidia Gita Lestari (AHKAM, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health concern in Indonesia, including in Probolinggo Regency. One preventive measure undertaken is the Mosquito Nest Eradication Program (Program Pemberantasan Sarang Nyamuk or PSN) 3M Plus, which involves the role of jumantik (mosquito larvae monitoring) cadres and active community participation. However, public satisfaction with the program's implementation remains suboptimal. This study aims to analyze the influence of health service quality, specifically the quality of jumantik cadre socialization and the quality of program implementation on community satisfaction in Asembagus Village, Kraksaan District, Probolinggo Regency. A quantitative inferential method was used, with data collected through questionnaires, observations, and documentation. A total of 138 respondents were selected using the Slovin formula from a population of 210 households. Regression analysis results show that the quality of PSN 3M Plus program implementation has a significant effect on community satisfaction (sig. 0.004 < 0.05), whereas the quality of jumantik cadre socialization does not (sig. 0.597 > 0.05). The coefficient of determination (R²) value of 6.4% indicates that most of the variation in community satisfaction is influenced by factors outside the studied variables. The main conclusion of this study is that improving field-level implementation quality—including accuracy, community participation, and program sustainability is key to the program’s success. The implications highlight the need for more interactive socialization strategies and community-based health services to enhance DHF prevention efforts and increase public satisfaction.